The 2021 Bigelow Institute for Consciousness Studies (BICS) Essay Contest - Kelleher, Colm; Bigelow, Robert (Journal of Scientific Exploration, 2022)
BICS was founded in 2020 to communicate, facilitate, educate, and organize scientific research and exploration into the survival of human consciousness (SOHC) after permanent bodily death. In early 2021 BICS announced an essay contest on the best evidence for survival of human consciousness with $950,000 in prizes. Essay contestants were tasked to present evidence for SOHC after death beyond a reasonable doubt. “Beyond a reasonable doubt” is the most demanding and rigorous burden of proof in the criminal justice legal system and BICS challenged essay contestants to achieve this very high bar in order to maximize the focus on presentation of evidence from as many directions and sources as possible. By December 2020, seven respected judges from the research and academic communities were recruited. BICS received 1300 applications from all continents and invited 264 authors and groups of authors to submit essays. 204 essays were received from 38 countries. Following an intensive five-month judging process, a large group of essays was down-selected. So high was the standard among the dozens of essays that the judges had difficulty in choosing three essays for the top prizes. After several more rounds, eventually 29 essays were chosen and the prize money was increased from $950,000 to $1,800,000. Prizes were awarded at a gala in Las Vegas on December 4, 2021. Following the conclusion of the BICS essay contest, the organization is preparing for another major program. On September 1, 2022, BICS will unveil “Challenge 2023,” which is a targeted grants program that is aimed at funding research proposals on SOHC with a particular focus on contact and communication with the afterlife.